Determining Factors in Handling Incidents Impacting Business Continuity in LRT Jabodebek Division - Nugrahaning Widhi, Diahayu; Novianti, Tanti; Aruddy, Aruddy (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Operational continuity is crucial for rail-based public transportation systems because of their complexity and interconnection. This study assesses the coherence of Business Continuity Management/Business Continuity Plan (BCM/BCP) components and identifies key criteria for the establishment of BCM/BCP in the LRT Jabodebek Division of PT Kereta Api Indonesia (Persero). A mixed-methods approach was utilized, integrating document analysis, in-depth interviews, Focus Group Discussions (FGDs), and the Analytical Hierarchy Process (AHP). The results demonstrate that current BCM/BCP-related papers have not been cohesively integrated and are deficient in essential continuity components, such as Business Impact Analysis (BIA), Recovery Time Objectives (RTOs), and quantifiable continuity metrics. The AHP results indicate that Human Resources is the predominant criterion (41%), succeeded by Systems and Technology (25%), Infrastructure (15%), External Factors (11%), and Operations (7%). The Integrated Business Impact Analysis (BIA) has been identified as the foremost strategic choice. These findings underscore the significance of organizational preparedness, continuity governance, and human-centered resilience in sustaining operational continuity within highly automated railway systems.